إشكالية المصطلح في الدرس البلاغي الانزياح في منهاج اللغة العربية بالثانوي التأهيلي نموذجا: The Problem of The Term in The Balaghah Al-Inziyah in The Arabic Language Curriculum in Secondary School - Driss Jamil (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2021)
The term occupies an important place in the communication system in general, and in various fields of knowledge, but its importance increases when it comes to the educational field ; Through it, knowledge is obtained, and perceptions are formed, so any defect in its development, transfer, or use would impede the teaching-learning process, or create gaps in the knowledge structures of learners. Awareness of this importance ; We decided to address in this scientific paper the problem of using the modern linguistic term in the rhetorical lesson in the Arabic language curriculum, in the conduct of arts and sciences in secondary qualifying education through the “displacement” model. This research is qualitative and library research in a descriptive method. The data in this research comes from written documents, traditional and contemporary books related to the research topic. This research relied on two data analysis methodologies. The result: The process of developing the modern linguistic term must be subject to a precise scientific method, away from the conflict between the ancient and the modern. The guidance in the curriculum is the way for every reform process. It has become imperative for curriculum developers, researchers, scholars and those interested in the two issues: critical and pedagogical knowledge to unite efforts to overcome the dilemma of the multiplicity of labels in the rhetorical lesson, and the problem of the multiplicity of Arabic interviews for the same term.